Diagnostic accuracy of the T-MACS decision aid with a contemporary point-of-care troponin assay. Issue 10 (12th January 2019) - Body, Richard; Almashali, Malak; Morris, Niall; Moss, Phil; Jarman, Heather; Appelboam, Andrew; Parris, Richard; Chan, Louisa; Walker, Alison; Harrison, Mark; Wootten, Andrea; McDowell, Garry
Abstract : Objectives: The rapid turnaround time of point-of-care (POC) cardiac troponin (cTn) assays is highly attractive for crowded emergency departments (EDs). We evaluated the diagnostic accuracy of the Troponin-only Manchester Acute Coronary Syndromes (T-MACS) decision aid with a POC cTn assay. Methods: In a prospective diagnostic accuracy study at eight EDs, we included patients with suspected acute coronary syndromes (ACS). Blood drawn on arrival and 3 hours later was analysed for POC cTnI (i-Stat, Abbott Point of Care). The primary outcome was a diagnosis of ACS, which included both an adjudicated diagnosis of acute myocardial infarction (AMI) based on serial laboratory cTn testing and major adverse cardiac events (death, AMI or coronary revascularisation) within 30 days. Results: Of 716 patients included, 105 (14.7%) had ACS. Using serial POC cTnI concentrations over 3 hours could have 'ruled out' ACS in 198 (31.2%) patients with a sensitivity of 99.0% (95% CI 94.4% to 100.0%) and negative predictive value 99.5% (95% CI 96.5% to 99.9%). No AMIs were missed. T-MACS 'ruled in' ACS for 65 (10.4%) patients with a positive predictive value of 91.2% (95% CI 82.1% to 95.9%) and specificity 98.9% (97.6% to 99.6%). Conclusion: With a POC cTnI assay, T-MACS could 'rule out' ACS for approximately one-third of patients within 3 hours while 'ruling in' ACS for another 10%. The rapid turnaround time and portability of the POC assay make this an attractive pathway for use in crowded EDs or urgent care centres. Future work should also evaluate use in the prehospital environment.